A modified correlation in principal component analysis for torrential rainfall patterns identification - Shazlyn Milleana Shaharudin (Tanjong Malim, 2020)
A modified correlation in principal component analysis for torrential rainfall patterns identification by Shazlyn Milleana Shaharudin